THE EXPLOITATION OF GROUP WORK TO INCREASE THE 4TH AND 5TH GRADERS’ MOTIVATION IN CLASSROOM TO STUDY ENGLISH - Bùi, Thị Quỳnh Trang (2020)
The modern language teaching approach puts a strong emphasis on communicative language teaching and learner-centered activities. Therefore, group work has been worldwide applied in English Language Teaching. In teaching English to children in Vietnam, group work has recently utilized but only in a few learning centers in big cities. In attempts to prove the effectiveness of group work, the researcher investigated the use of group work in specifically two specific English classes for children in organization X, Hanoi, which provide learners with an ideal learning environment.